Analyzing economic tradeoffs of water use in the Nam Ngum River Basin, Lao PDR - Bartlett, R.; Baker, J.; Lacombe, Guillaume; Douangsavanh, Somphasith; Jeuland, M. (Duke University. Nicholas Institute for Environmental Policy Solutions, 2012)
This paper develops a hydro-economic optimization modeling framework to assess the economic consequences and potential trade-offs of various infrastructure development and policy pathways in the Nam Ngum Basin (Lao PDR). We considered whether large shifts in water resource demands in a relatively water abundant basin could induce meaningful economic trade-offs among water uses, including hydropower generation, irrigation expansion, flood control, and transboundary water transfer objectives. We constructed a series of sensitivity scenarios under dry, average, and wet hydrologic conditions with varying levels dam development, irrigated agricultural expansion, agricultural returns, flood control storage restrictions, and water diversions to Northeast Thailand. We also considered how flows into the Mekong would be affected by these collective developments. In general, results indicate that tradeoffs between hydropower production, irrigation, and flood control are modest. Hydropower and agricultural expansion are found to be complimentary under high levels of water availability, even with the most ambitious level of irrigation expansion. Allowing for flood control by maintaining reduced storage levels in the reservoir that is largest and furthest downstream on the Nam Ngum (NN1) has a minimal effect on economic output and decreases total system hydropower by less than 1%. However, economic outcomes are highly dependent on water availability and economic returns to irrigated agriculture. System hydropower was greatly reduced, and inter-basin transfer projects induced large economic costs under dry conditions. These results on seasonal impacts illustrate the importance of accounting for climate variability and potential hydrologic change in cost-benefit analysis of infrastructure projects, even in watersheds that are relatively water abundant.